Aviation Industry and Covid-19: New Normal in the Pandemic Era, the Experience of Passenger, Post-Pandemic Traveling, and Long-term Impact on the Airlines - Bharatish S.; Nur Shazwanni Rosmi; Nur Syabani; Nur Syafiqah Hasnuddin; Nur Syahieera (AIBPM Publisher, 2023)
The Covid-19 pandemic is currently ravaging the entire world and the aviation industry is one of the hardest hit industries. This paper aims to analyze and understand the change in consumers behavior with regards to the aviation industry due to the Covid-19 pandemic. A questionnaire was administered to 100 respondents to glean insights into passenger preferences and travel decisions. The results reveal a strong willingness among respondents to travel when a cure for COVID-19 becomes available, emphasizing the crucial role of medical solutions in boosting passenger confidence. Additionally, the importance of low COVID-19 case counts at destinations and the tension between safety measures and passenger freedom is evident. Moreover, the research highlights the value passengers place on convenience and adaptability, as well as their evolving expectations regarding personal space and hygiene. These findings provide comprehensive insights into the complex dynamics of passenger behavior and satisfaction within the aviation industry during the pandemic, offering valuable reference points for industry stakeholders and policymakers.